The world in the post-pandemic time: Geopolitical and geostrategic implications for a new world order - Tavares, António (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
After the pandemic, which paralyzed the planet socially and economically, forcing governments to impose confinements, the world awoke, two years later, with a “special military operation” by Russia against Ukraine. This sign of aggression raised the spectre of a world conflict with Europe as its theatre of operations. The imposition of economic sanctions and the fact that the UN was unable to act highlighted that the international order may have been jeopardised. Tension with NATO and its member states supporting the Ukrainian cause has created conditions to accelerate this conflict.